MODEL PENINGKATAN KINERJA SDM MELALUI MOTIVASI INSTRINSIK DAN MOTIVASI EKSTRINSIK DI SEKRETARIAT DAERAH KABUPATEN KONAWE - Tatik Sunarni (Jurnal Riset Bisnis Indonesia, 2014)
Human resource in globalization area is very decided of success in the organization purpose. So thatperformance is very importance in which to get the improvement of human resource performance.This study is purposedto measure the improvement of human resource performance in SekretariatDaerah distric of Konawe. Variable are used inthis studyare variables Intrinsic Motivation, ExtrinsicMotivation and Affective Commitment and job performance. Variables Intrinsic Motivation andExtrinsic Motivation is as independent variable and variable of Affective Commitment is as variableindependent and dependent. The other variable is job performance. Sampling technique of this studyis census method with total 125 questionnaires were circulated, out of which 99 questionnairesreturned back. Analyzing data used in this study is using software analyzing smart PLS (Partial LeastSquare). The finding of this study concluded that the Intrinsic Motivation have positive significance toAffective Commitment, Intrinsic Motivation have Positive non Significance to job performance, whilethe variable of Extrinsic Motivation have positive significance to Affective Commitment, ExtrinsicMotivation have positive significance to Job Performance and the variable of Affective Commitmenthave positive Significance to Job Performance.Keywords : Intrinsic Motivation, Extrinsic Motivation, Affective Commitment, Job Performance